ANALISIS MINAT MASYARAKAT TERHADAP PRODUK KREDIT CEPAT AMAN (KCA) DI PT. PEGADAIAN CO-LOCATION CIBARUSAH, KABUPATEN BEKASI - Widya Suci Lestari; Puspita Romadhona (Jurnal Ilmiah Global Education, 2023)
This study aims to determine public interest in Fast Secured Credit products at PT. Pegadaian Co-Location Cibarusah, Bekasi Regency. This research uses descriptive qualitative. Respondents in this study were 20 customers of PT. Pegadaian Co-Location and 1 employee of PT. Pegadaian PT. Pegadaian is the Pawn Manager of Kota Wisata Branch. Data collection methods used are observation, interviews, and documentation. The collected data were analyzed descriptively by conducting interviews showing the public's interest in Fast Secured Credit products at PT. Pegadaian Co-Locations in Cibarusah, Bekasi Regency There are quite a lot of. It is known that this Co-Location streamlines customer time in making transactions at Pegadaian outlets. Shown by the turnover that has been achieved in the last 1 year PT. Pegadaian Co-Location Cibarusah, Bekasi Regency increased by 11.37% with a marketing team that PT. Pegadaian owns and marketing strategy used by PT. pawnshop. However, it does not rule out the strategy used by PT. This pawnshop was changed to increase the interest of increasingly diverse customers and increasingly sophisticated technological advances.